2022
DOI: 10.3390/ijerph19148717
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Optimization and Oxygen-Enrichment Effect of Ventilation Scheme in a Blind Heading of Plateau Mine

Abstract: There are abundant mineral resources in plateau areas, but it is difficult to extract them safely because the problem of hypoxia in plateau mines seriously affects the life and health of workers. In order to address the problem of hypoxia in the blind heading of a plateau metal mine, a three-dimensional roadway model was established based on field data of the Pulang copper mine in Yunnan province, China. The computational fluid dynamics (CFD) method was used to explore the optimal type of oxygen supply duct ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…Обеспечение надежности эффективного проветривания тупиковых горных выработок является одной из ключевых задач рудничной вентиляции, регулируемых правилами безопасности ведения подземных горных работ 1 и привлекающих особое внимание отечественных [1][2][3] и зарубежных [4][5][6] исследователей. В литературе рассматривались особенности проветривания тупиковых горных выработок при различных способах выемки полезного ископаемого [7,8], а также вопросы методологии моделирования аэрологических процессов в тупиковых выработках, связанные, в частности, с корректным выбором моделей турбулентности [6], применением подходов, основанных на дискретном моделировании [9].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Обеспечение надежности эффективного проветривания тупиковых горных выработок является одной из ключевых задач рудничной вентиляции, регулируемых правилами безопасности ведения подземных горных работ 1 и привлекающих особое внимание отечественных [1][2][3] и зарубежных [4][5][6] исследователей. В литературе рассматривались особенности проветривания тупиковых горных выработок при различных способах выемки полезного ископаемого [7,8], а также вопросы методологии моделирования аэрологических процессов в тупиковых выработках, связанные, в частности, с корректным выбором моделей турбулентности [6], применением подходов, основанных на дискретном моделировании [9].…”
Section: Introductionunclassified
“…В литературе рассматривались особенности проветривания тупиковых горных выработок при различных способах выемки полезного ископаемого [7,8], а также вопросы методологии моделирования аэрологических процессов в тупиковых выработках, связанные, в частности, с корректным выбором моделей турбулентности [6], применением подходов, основанных на дискретном моделировании [9]. Исследовались различные усложняющие факторы, например, непрерывное выделение пыли при работе комбайна [10], газовыделение в выработанном пространстве [8,11], рассмотрение переноса кислорода как отдельного компонента воздушной среды [5]. Вводились и исследовались различные критерии для определения эффективности проветривания тупиковых выработок [4].…”
Section: Introductionunclassified
“…Wang et al 26 demonstrated that at different altitudes, the oxygen concentration in mine tunnels would initially increase and then decreased with increasing distance to the excavating face. Li et al 27 showed that the position of the forcing duct is the most influential factor for oxygen distribution in mine tunnels. In the field of civil architecture, researchers have proposed novel facilities for oxygen diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [20] developed a multi-component fluid model for diffusive oxygen supply in single-headed tunnels to optimize the oxygen supply method and ventilation system design, and concluded that the oxygen mass fraction distribution in single-headed tunnels showed a similar trend of increasing and then decreasing at different altitudes. Li et al [21] used computational fluid dynamics methods to explore the optimal type of oxygen supply pipe outlet based on field data from the Pulang Copper Mine in Yunnan Province, revealing the oxygen diffusion pattern affecting different ventilation factors. As can be seen from the above, diffuse type oxygen supply is widely used in high altitude areas and has the advantage of covering a wide area and increasing oxygen concentration significantly.…”
Section: Introductionmentioning
confidence: 99%